DIVERSIFICATION OF SCIENTIFIC KNOWLEDGE IN THE AGE OF INFORMATION - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2009)
The article investigates peculiarities of diversification of scientific knowledge under the circumstances of informatization of different kinds of social practice.